Lemon seeds as green coating material for mitigation of mild steel corrosion in acid media: Molecular dynamics simulations, quantum chemical calculations and electrochemical studies - Pal S.; Ji G.; Lgaz H.; Chung I.-M.; Prakash R. (My University, 2025)
Natural materials are the subject of high priority for corrosion scientists, now a day. Various natural materials have been used to date for corrosion protection of metals. However, their utilizations have been done either in inhibition (mostly) or coating applications (only in composite form). In present work, lemon seed (alone) is used for inhibition as well as coating protection of mild steel (MS) corrosion in acid media. Aqueous extract of lemon seed (ALS) is used as inhibitor, whereas chloroform extract of lemon seed (CLS) is used to form wet (CLSW) and dry (CLSD) coating on MS substrate. Characterizations of ALS, CLSW and CLSD have been done by UV–visible spectroscopy, FTIR spectroscopy, HRSEM, EDAX and AFM analysis. Corrosion testing of both extracts has been performed in 1 M HCl by ac impedance measurements (AIM) and Tafel polarization curves (TPC). The results show that ALS gives very low inhibition of MS corrosion (~45%), while MS coated with CLSD/CLSW provide high efficiency protection (~98%) to the substrate. Theoretical analysis tools, i.e., molecular dynamics simulations and quantum chemical calculations, are also used to determine corrosion properties of lemon seed molecule, which suggest that lemon seed can be prominent material for prevention of MS corrosion. © 2020 Elsevier B.V.